On a Certain Quadratic Character Sums of Ternary Symmetry Polynomials modp - Yuanyuan Meng (Journal of Mathematics)
In this article, we are using the elementary methods and the properties of the classical Gauss sums to study the calculating problem of a certain quadratic character sums of a ternary symmetry polynomials modulo p and obtain some interesting identities for them.